Prevalence and factors associated with preterm births among postnatal mothers at Soroti Regional Referral Hospital, Eastern Uganda - Pamella R. Adongo; J. Wandabwa; J. Epuitai; G. Epaku; F. Alaroker; J.P. Waako; P. Olupot-Olupot (Elsevier, 2023)
Background: Globally, prematurity is the leading cause of death in neonates and therefore a major contributor to the under 5-year mortality. The study assesses the prevalence and risk factors associated with preterm birth at a Regional Referral Hospital in Eastern Uganda. Methods: This was a descriptive cross-sectional study conducted at a Regional Referral Hospital in Eastern Uganda. A questionnaire was used to capture data on maternal socio-demographic features, and obstetrical causes of preterm birth. Additional information was got from maternal medical records. In total, 350 mother-baby pairs were studied. Bivariate and multivariate logistic regression models were fitted so as to establish the factors associated with preterm birth. A p-value < 0.05 was considered statistically significant. Results: Prevalence of preterm birth at Soroti Regional Referral Hospital was 24.6% (86/350). Factors associated with preterm birth included: Fewer than 3 antenatal attendances (aOR = 3.115, 95% CI [1.659-5.849], P = 0.038), twin gestation (aOR = 6.973, 95% CI [1.128-43.097], P = 0.016), antepartum hemorrhage (aOR = 4.743, 95% CI[806-12.458], P < 0.001) and PPROM (aOR = 18.902, 95% CI[7.267-49.167], P < 0.001). Maternal mid upper arm circumference (MUAC) measurement ≥24 cm was a protective factor against preterm birth (aOR = 0.155, 95% CI[0.0686-0.352], P < 0.001). Conclusion: Preterm births in Soroti-RH in Eastern Uganda were associated with poor maternal nutrition status, low antenatal attendance, twin gestation, antepartum hemorrhage, and preterm premature rupture of membranes. Health education on proper nutrition and routine monthly antenatal visits by healthcare workers is important for early screening and detection of high risk pregnancies.